1999
DOI: 10.2486/indhealth.37.382
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Response to Psychological Test in Hand-Arm Vibration Syndrome Patients Assessed by Frequency Domain Analysis.

Abstract: To investigate heart rate variability in response to psychological tests (Japanese version of Stroop color word test and mirror drawing test) in 29 hand-arm vibration syndrome (HAVS) patients, 16 of them with vibration-induced white finger (VWF) and 13 without VWF, and 10 healthy controls of similar age, heart rate variability during spontaneous and deep (6 cycles a minute) breathing in supine position before and after exposure to the psychological tests was examined calculating frequency domain components suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that low frequency (LF: 0.04-0.15 Hz) changes represent activity in the cardiac sympathetic nervous system (SNS), high frequency (HF: 0.15-0.40 Hz) changes represent the activity of the cardiac PNS, and the LF/HF ratio represents the balance of the cardiac ANS [18]. In 1999, Laskar et al compared the changes in LF, HF and LF/HF ratio during deep breathing in hand-arm vibration syndrome patients and healthy control subjects [19]. In addition, it is also reported that the HF power increased significantly and the LF/HF ratio decreased significantly during Zen meditation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that low frequency (LF: 0.04-0.15 Hz) changes represent activity in the cardiac sympathetic nervous system (SNS), high frequency (HF: 0.15-0.40 Hz) changes represent the activity of the cardiac PNS, and the LF/HF ratio represents the balance of the cardiac ANS [18]. In 1999, Laskar et al compared the changes in LF, HF and LF/HF ratio during deep breathing in hand-arm vibration syndrome patients and healthy control subjects [19]. In addition, it is also reported that the HF power increased significantly and the LF/HF ratio decreased significantly during Zen meditation [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested in some studies that the autonomic nervous function, besides the peripheral circulation, peripheral nervous and musculoskeletal systems, might be affected due to exposure to hand-arm vibration and was assessed previously in hand-arm vibration syndrome (HAVS) patients by means of time domain analysis of heart rate variation, and measuring levels of plasma catecholamines and cyclic nucleotides [3][4][5][6][7] . It was observed that cold exposure activates the sympathetic nervous system to a higher degree in subjects with HAVS than in controls [8][9][10] .…”
mentioning
confidence: 99%